Fuzzy evaluation method using fuzzy rule approach in multicriteria analysis - Othman, Mahmod; Ku-Mahamud, Ku Ruhana; Abu Bakar, Azuraliza (2008)
A multicriteria analysis in ranking the quality of teaching using fuzzy rule is proposed. The proposed method uses the application of fuzzy sets and approximate reasoning in deciding the ranking of the quality of teaching in several courses.The proposed method introduces normalizing data which dampen the extreme value that exists in the data.The use of the model is suitable in evaluating situations that involve subjectivity, vagueness and imprecise information. Experimental results are comparable and the method performs better in some domains.